A matrix-free multilevel preconditioner for the generalized Stokes problem with discontinuous viscosity - Wichrowski, Michał; Krzyżanowski, Piotr (Journal of computational science, 2022)
In this paper we present a matrix-free multilevel solver for the generalized Stokes problem with discontinuous viscosity. The algorithm is based on the FGMRES iteration preconditioned with a block-smoothed multigrid method. Numerical experiments on unstructured grids indicate that for a broad range of smoother parameters, the convergence speed is only weakly dependent on both the number of unknowns and the jumps of the viscosity coefficient.
Gesehen am 02.11.2023